Gender, Media, and Mixed Martial Arts in Poland: The Case of Joanna Jędrzejczyk. (October 2016) - Jakubowska, Honorata; Channon, Alex; Matthews, Christopher R.
Recent growth in the media visibility of female combat sport athletes has offered a compelling site for research on gender and sport media, as women in deeply masculinized sports have been increasingly placed in the public spotlight. Although scholars in the Anglophone West have offered analyses of the media framing of this phenomenon, little work has been done outside these cultural contexts. Thus, in this article, we offer a qualitative exploration of how Joanna Jędrzejczyk, a Polish champion of the Ultimate Fighting Championship, has been represented in Polish media. Our findings reveal a relatively de-gendered, widely celebratory account, primarily framed by nationalistic discourse—findings we ascribe to both the particularities of the sport of mixed martial arts as well as the historic nature of Jędrzejczyk's success.